Understanding gifted adolescents : accepting the exceptional - Simpson, Joanna, 1980- (Lexington Books, 2015)
"Understanding Gifted Adolescents: Accepting the Exceptional addresses the basis of exclusive education for gifted adolescents from the theoretical perspective of social identity. Using the lens of social identity theory and adolescent development related to giftedness, this book builds the case for a curriculum for gifted adolescents. By providing a comprehensive foundation for exploring the concept of a more exclusive education scholastically, and debunking the "elitist" concept of gifted education, this book is a well-organized and clearly-structured exposition for the philosophy of gifted education, as well as a means of putting a curricular model into practice in American high schools. With pointed critiques of differentiated instruction in the general education classroom and the current trend of standardization and normalization in the current educational climate, a new philosophy for addressing gifted education is presented."--